JAMUR MIKORIZA ARBUSKULA PADA LAHAN TANAMAN JATI BERTUMPANGSARI TEBU - Corryanti Corryanti (JURNAL AGROTROPIKA, 2011)
This research aimed to investigate the diversity of arbuscular mycorrhizae fungi in teak plantation intercropped with sugarcane. The research was conducted at teak plantation of BKPH Tangen, Surakarta, Center of Java. Soil samples were composite, collected from 30 cm depth around teak trees, of three classes of teak growth i.e. low (6.8 m tall, 20 cm girth), medium (9.2 m tall, 2.25 cm girth), and high (11.6 m tall, 33.2 cm girth). The results showed that both the diversity and spore abundance of mycorrhiza fungi was low. We found 5 types of mycorrhizae fungi which 2 types belong to Gigaspora and 3 types belong to Glomus.  Key words: teak, sugarcane, multiple cropping, mycorrhizae, diversity, abundance.